Transformasi Industri Seni: Peran Teknologi dalam Ekonomi Kreatif - Alivia Rohmatun Nasifah; Betty Silfia Ayu Utami (Jurnal Ekonomi dan Bisnis Digital, 2025)
The transformation of the arts industry in the digital era which is influenced by technological developments, especially in the digitalization of works of art, distribution and marketing via digital platforms. Modern technologies, such as augmented reality (AR), virtual reality (VR), as well as blockchain, have opened up new opportunities for artists to create interactive art experiences, market works globally, and ensure ownership authentication through non-fungible tokens (NFTs). Digitization makes it easier to distribute works of art, allowing artists to reach a global audience without geographic boundaries. Additionally, technology has driven artistic product innovation, such as artificial intelligence (AI)-based applications for music and visual arts, which accelerate the creative process and increase global competitiveness. However, challenges such as copyright protection, unequal access to technology, and cultural adaptation to digital advances are issues that require serious attention. This article recommends strategic steps, including digital education for artists, strengthening copyright regulations, increasing access to technology in remote areas, and cross-sector collaboration to overcome these challenges. With this approach, it is hoped that digital technology can support the sustainable development of the arts industry without sacrificing the cultural value and authenticity of traditional art